Learning the left : popular culture, liberal politics, and informal education from 1900 to the present - Ramsey, Paul J. (Emerald Publishing Limited : Information Age Publishing, Inc., 2015)
Learning the Left examines the ways in which young people and adults learned (and continue to learn) the tenets of liberal politics in the United States through the popular media and the arts from the turn of the twentieth century to the present. This collection of essays foregrounds mass culture as an educational site; it is hoped that this focus on the history of the civic functions of the popular media and arts will begin a much-needed conversation among a variety of scholars, notably historians of education.